A Retrieval-Augmented Generation Framework for a Study Program Accreditation Question-Answering System - Putri, Rifki Afina; Nurramdhani, Helena I.; Hartati, Sri (Engineering, Technology & Applied Science Research, 2026)
Accreditation agencies play a crucial role in ensuring the quality of higher-education institutions by evaluating programs based on established standards and guidelines. However, accreditation processes often involve complex documents that applicants may find difficult to interpret, leading to repetitive inquiries and administrative burden. This study proposes an Artificial Intelligence (AI)-based Question-Answering (QA) system built using a Retrieval-Augmented Generation (RAG) architecture to support accreditation-related information services. The system is developed specifically in the Indonesian language, enabling users to understand accreditation documents more easily by retrieving authoritative content and generating contextually appropriate explanations. As a case study, we apply this approach to LAM INFOKOM, Indonesia's Independent Accreditation Agency for Informatics and Computing. Experimental results show strong retrieval performance, with a Mean Reciprocal Rank (MRR) of 0.88, and high-quality response generation, with a BERTScore F1 of 0.76 and a manual accuracy of 83.67%. These results demonstrate the effectiveness of the Indonesian RAG-based system in improving accreditation information services with the potential to reduce manual workloads.